Balloon pulmonary angioplasty outcomes in patients previously treated by pulmonary endarterectomy surgery are inferior to those of inoperable patients - Louise C. Kirkby; Matthew S. Rodgers; Liliana Amaral‐Almeida; Karen Sheares; Mark Toshner; Katherine Bunclark; Aleksandra Bartnik; Dolores Taboada; Choo Ng; Fouad J. Taghavi; Steven Tsui; John E. Cannon; et al. (Pulmonary Circulation, 2023)
Abstract Pulmonary endarterectomy (PEA) may not achieve full clearance of vascular obstructions in patients with more distal chronic thromboembolic pulmonary hypertension (CTEPH). Balloon pulmonary angioplasty (BPA) may be indicated to treat these residual vascular lesions. We compared whether patients post‐PEA (PP) treated by BPA derived similar benefit to those who had inoperable CTEPH (IC), and assessed predictors of BPA response after surgery. We treated 109 patients with BPA—89 with IC and 20 PP. Serial right heart catheterization performed at baseline (immediately before BPA) and 3 months after completing BPA, compared pulmonary vascular resistance (PVR), mean pulmonary artery pressure (mPAP) as well as change in WHO functional class and 6‐minute walk distance. We also assessed the impact of total thrombus tail length (TTTL) from photographed PEA surgical specimens and PP computed tomography pulmonary angiography (CTPA)‐quantified residual disease burden on BPA response. PP and IC groups did not differ significantly in terms of demographics, baseline hemodynamics or procedural characteristics. However, IC derived greater hemodynamic benefit from BPA: ΔPVR (−27.9 ± 20.2% vs. −13.9 ± 23.9%, p < 0.05) and ΔmPAP (−17.1 ± 14.4% vs. −8.5 ± 18.0%, p < 0.05). There was a negative correlation between pre‐BPA PVR and TTTL (r = −0.47, p < 0.05) which persisted post‐BPA. PVR, mPAP, WHO FC and 6MWD were not improved significantly post‐BPA in PP patients. BPA response was not related to TTTL terciles or CTPA‐quantified residual disease burden. Patients PP experienced inferior response to BPA, despite similar baseline and procedural characteristics to IC. BPA does not abolish the relationship between TTTL and postsurgical PVR in PP patients, suggesting that BPA is less effective in treating residual PH after surgery in an experienced surgical center.